An Empirical Study on the Impact of Brand Loyalty in Remembering Slogans - Silveira, Paulo Duarte (2020)
Purpose: This paper examines the influence of brand loyalty on the individuals’ capacity to recall and recognize brand slogans. Design/Methodology/Approach: Empirical quantitative research, gathering data via an online questionnaire among 370 costumers of three telecom B2C service providers in Portugal. Findings: In general terms, the influence of brand loyalty on the ability of the customers to recall and recognize slogans was not verified. Practical implications: For a brand interested in raising its slogan awareness, either by recall or recognition, the level of marketing efforts should not vary according to the customer loyalty degree. Originality/Value: The study contributes to the analysis of an influence not yet explored in the previous studies dedicated to improving slogans’ effectiveness.